Numerical analysis of supercritical CO2 dry gas seals with phase transitions. Issue 7 (6th June 2022) - Zhang, Cong; Jiang, Jinbo; Peng, Xudong
Abstract : Purpose: This paper aims to acquire the phase distribution and sealing performance of supercritical carbon dioxide (SCO2 ) dry gas seals with phase transitions. Design/methodology/approach: The SCO2 spiral groove dry gas seal is taken as the research object. The finite differential method is applied to solve the governing equations. Furthermore, the phase distribution and the sealing performance are obtained. Compared to the ideal gas model, the effect of phase transitions on sealing performance is also explored. Findings: Vaporization is likely to occur near the inner radius when SCO2 dry gas seals are operated near the critical point. Whether phase transitions are considered in the model affects the sealing performance seriously. When phase transitions are considered, the sealing performance depends significantly on the working conditions, and unexpected results are produced when inlet conditions approach the critical point. Originality/value: The numerical model for SCO2 dry gas seals with phase transitions is established. The phase distribution and the sealing performance of SCO2 dry gas seals are explored.